Just Checking It Out? Motivations for and Behavioral Associations With Visiting “Slutpages” in the United States and Australia - Clancy, Elizabeth M.; Maas, Megan K.; March, Evita; Howard, Dominika; Klettke, Bianca (Frontiers in Psychology, 2021)
Slutpages are a pernicious form of online image-based sexual abuse, where (sexual) images of women are presented for male groups to rate and comment. Despite media and public concern, slutpages have garnered limited empirical study. This paper offers the first analysis of slutpage visitation motivations across U.S. and Australian samples. Participants were an online convenience sample of 1148 young adults aged 18 to 29 years (M = 22.54, SD = 2.50; 53.0% women, 47.0% men; resident in the U.S. (53.8%) or Australia (46.2%)), who completed an online questionnaire. Overall, 23% of U.S. and 16% of Australian respondents had visited slutpages, with men more likely than women. Slutpage visitation was uniquely associated with gender (men more likely to visit), country (Americans more likely to visit) and sext dissemination. Interestingly, cyberbullying perpetration was associated with reduced odds of slutpage visitation. Motivations differed by gender, with men most likely (80%) to visit to “check it out” while women were equally likely to check it out (41%) or to see if they were depicted (36%). For men, unique predictors of slutpage visitation were having disseminated and received disseminated sexts, lower levels of anxiety and reduced likelihood of cyberbullying perpetration. For women, slutpage visitation was uniquely associated with being a U.S. resident, sext dissemination victimization, receipt of disseminated sexts and higher levels of anxiety. Our findings confirm that slutpages appear to be a highly gendered form of online image-based sexual abuse, and may have important mental health outcomes, given associations with increased anxiety. Our results support the need for slutpage education for adolescents and young adults to address social and peer norms that encourage and support non-consensual use of intimate images.